Decreased platelet specific receptor expression of P-Selectin and GPIIb/IIIa predict future non-surgical bleeding in patients after left ventricular assist device implantation - Klaeske, Kristin; Meyer, Anna L.; Saeed, Diyar; Eifert, Sandra; Jawad, Khalil; Sieg, Franz; Haunschild, Josephina; Borger, Michael A.; Dieterlen, Maja-Theresa (International journal of molecular sciences, 2022)
Non-surgical bleeding (NSB) is one of the major clinical complications in patients under continuous-flow left ventricular assist device (LVAD) support. The increased shear stress leads to an altered platelet receptor composition. Whether these changes increase the risk for NSB is unclear. Thus, we compared the platelet receptor composition of patients with (bleeder group, n = 18) and without NSB (non-bleeder group, n = 18) prior to LVAD implantation.
Gesehen am 15.11.2022